Physics for game developers : science, math, and code for realistic effects - Bourg, David M. (Libros electrónicos en Ebscohost, 2013)
If you want to enrich your game's experience with physics-based realism, the expanded edition of this classic book details physics principles applicable to game development. You'll learn about collisions, explosions, sound, projectiles, and other effects used in games on Wii, PlayStation, Xbox, smartphones, and tablets.